IPTEKS PELAPORAN PERSEDIAAN PADA PUPRD SULUT - Mangarey, Reyfando Bilgery; Mose, Gabriela Nikita; Kalangi, Lintje (Universitas Sam Ratulangi, 2018)
Government Regulation No. 71 of 2010 concerning Government Accounting Standards in recording inventory can realize the performance performed by government agencies, especially in the presentation of inventory reporting. The purpose of this study was to determine the government accounting standard policies in reporting inventory at the Office of Public Works and Regional Spatial Planning of North Sulawesi Province according to Government Regulation Nomber. 71 of 2010 based on PSAP 05 concerning Inventory Accounting and the method used in this research is the service inventory reporting analysis method Public Works and Regional Spatial Planning of North Sulawesi Province with the technique of science and technology collecting inventory data and conducting analysis. The results of this study indicate that inventory reports at the Public Works Agency and Regional Spatial Planning of North Sulawesi Province are stated to be in accordance with government accounting standards.Keywords: Policies, government regulations, Inventory Reporting